Effect of pretreatment with collagen crosslinkers on dentin protease activity. Issue 8 (August 2015) - Seseogullari-Dirihan, R.; Mutluay, M.M.; Vallittu, P.; Pashley, D.H.; Tezvergil-Mutluay, A.
Graphical abstract